Sustainable competitiveness through community empowerment and the success factors of SMEs? - Hayu Kartika; Hartrisari Hardjomidjojo; Machfud Machfud; Endang Warsiki (SINERGI, 2026)
This study aims to examine the relationship between sustainable competitiveness and community empowerment in the context of small and medium enterprises (SMEs) by conducting a systematic literature review using the PRISMA guidelines. The review identified relevant studies published between 2021 and 2025 in the Scopus database and analyzed them using the VOS Viewer bibliometrics tool. This study explores the role of empowerment in improving Sustainable Competitiveness. Findings show that the topics of sustainable competitiveness and community empowerment are still rarely discussed in an integrated manner, although both are significantly interrelated. The analysis identified six main dimensions that contribute to sustainable competitiveness in SMEs: Economic, Social, Environmental, Technological, Organizational, and Human Resources that correlate with sustainable competitiveness in SMEs. In various literature, sustainable competitiveness in SMEs is often discussed and has a close relationship with the use of technology in SMEs businesses. However, on the other hand, it also needs to be supported by the role of the community, which is included in the social dimension, which also plays an important role in SMEs that support business sustainability, foster cooperation networks, and improve the welfare of local communities. These findings provide a basis for insight and information to develop targeted business strategies and public policies aimed at enhancing sustainable competitiveness in SMEs through community engagement.